Combined process of hot stamping and mechanical joining for producing ultra-high strength steel patchwork components. (November 2020) - Mori, Ken-ichiro; Kaido, Tomoya; Suzuki, Yasutaka; Nakagawa, Yuki; Abe, Yohei
Graphical abstract: Highlights: A main blank and patch were uniformly heated without overlapping in a furnace. Interlocks for joining were created by local buckling during hot stamping. Appropriate intermetallic compound was created on the surface of the patchwork part. Tapered and zinc-coated patchwork parts were successfully produced. A mechanical joining using a punched patch was developed as another process. Abstract: A combined process of hot stamping and mechanical joining for producing ultra-high strength steel patchwork components was developed. The main blank and patch were uniformly heated side by side without overlapping in a furnace, and then, the overlapped main blank and patch were hot-stamped. An appropriate layer of intermetallic compounds was generated on the surface of the patchwork part by uniform heating. The main blank locally came in the space of the die step due to buckling, and interlocks for joining the main blank and patch were created. To increase the amount of interlock, both edges of the main blank are fixed with the stoppers in the latter stage of forming, and then, the main blank is compressed in the planar direction with the punch and die. For a length difference for main blank of 16 mm and a space length of die step of 5.1 mm, the gap between the main blank and patch was almost zero, the main blank and patch were successfully laser-welded, and the laser-welded patchwork part had sufficient collapse load and punch stroke. Tapered and zinc-coated patchwork parts were successfully produced. Another mechanical joining process using a punched patch was developed.